In vitro monocyte maturation as a prediction of survival in squamous cell carcinoma of the lung. Issue 6 (June 1981) - Dent, R G; Cole, P
Abstract : In vitro monocyte maturation was studied in patients with squamous cell carcinoma of the lung–limited to the ipsilateral hemithorax in 30 and more extensive in 40. The patients were studied prospectively and initial monocyte maturation was correlated with survival. Monocyte maturation in patients with limited disease before treatment ranged from 3.1 to 57.6% with a median value of 21.4%. The survival of those patients in whom monocyte maturation was less than the normal range (less than 30.4%) was significantly shorter than the survival in those with normal maturation ( p less than 0.05). Four of the five patients whose initial maturation was less than 10% proved to be inoperable at surgery. Patients with extensive disease had monocyte maturation ranging from 2.4 to 52.9% with a median value of 13.2%, significantly lower than in those with limited disease (p less than 0.025). Patients with extensive disease and low monocyte maturation survived a significantly shorter time than those with normal maturation ( p less than 0.005). The depression of monocyte development may explain the finding of negative delayed hypersensitivity skin reactions in many patients with lung carcinoma and may prove useful as an index of prognosis.